2019
DOI: 10.3390/ma12101617
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Titanium Nanotube Reinforced Cementitious Composites: Mechanical Properties, Microstructure, and Hydration

Abstract: In recent years, nano-reinforcing technologies for cementitious materials have attracted considerable interest as a viable solution for compensating the poor cracking resistance of these materials. In this study, for the first time, titanium nanotubes (TNTs) were incorporated in cement pastes and their effect on the mechanical properties, microstructure, and early-age hydration kinetics was investigated. Experimental results showed that both compressive (~12%) and flexural strength (~23%) were enhanced with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…There are limited studies on the flexural strength of PC in comparison with other endodontic cements [ 78 , 79 ]. Contamination with blood or saliva has no significant effect on the flexural strength of Portland cement [ 80 ].…”
Section: Physicomechanical Propertiesmentioning
confidence: 99%
“…There are limited studies on the flexural strength of PC in comparison with other endodontic cements [ 78 , 79 ]. Contamination with blood or saliva has no significant effect on the flexural strength of Portland cement [ 80 ].…”
Section: Physicomechanical Propertiesmentioning
confidence: 99%
“…Wang et al [13] reported increased hydration rate dramatically during the early stages which gradually declined later. It is also evident from the study by Jee et al [11] that the degree of hydration of 55.75% for both pure C 3 S and n-TiO 2 incorporated C 3 S. It could be inferred that the role of n-TiO 2 is primarily an inert material enhancing dispersion, thereby promoting heterogenous nucleation.…”
Section: Depict Thementioning
confidence: 86%
“…Concrete smeared with n-TiO 2 serve as a photocatalytic material while concrete modified with different weight percent of n-TiO 2 forms high quality concrete [10,11]. Fineness, specific surface area of n-TiO 2 and percentage of replacement influence the hydration process of cement by facilitating hydration products precipitation at more sites [12,13].…”
Section: Hydration and Setting Properties Of N-tio 2 Concretementioning
confidence: 99%
“…To observe the variation of the mechanical properties of the cement paste with hydration time, the compressive and splitting tensile strength of the specimens were tested after curing 1, 3, 7, and 28 days, respectively [ 57 ]. The compressive and splitting tensile strengths of the hydrated cement paste were measured using a micro-compressive machine (Deben, Micro-Compressive Machine, Edmunds, Suffolk, UK) [ 58 ]. Figure 2 shows a schematic of the compressive and splitting tensile strength tests [ 57 , 59 ].…”
Section: Methodsmentioning
confidence: 99%